Sitagliptin protects renal glomerular endothelial cells against high glucose-induced dysfunction and injury. Issue 1 (1st January 2022) - Xu, Liang; Shao, Fengmin
ABSTRACT: Sitagliptin is a well-established anti-diabetic drug that also exerts protective effects on diabetic complications. Previous work reveals that sitagliptin has a protective effect on diabetic nephropathy (DN). Vascular impairment frequently occurs in diabetic renal complications. Here, we evaluated the protective function of sitagliptin in human renal glomerular endothelial cells (HrGECs) under high glucose (HG) conditions. Expressions of the pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-8 (IL-8) were assessed using real-time PCR and ELISA. Endothelial cells permeability was assayed using the fluorescein isothiocyanate dextran (FITC-dextran) and trans-endothelial electrical resistance (TEER) assay. The results show that sitagliptin mitigated HG-induced oxidative stress in HrGECs with decreased levels of mitochondrial reactive oxygen species (ROS), Malondialdehyde (MDA), and 8-hydroxydeoxyguanosine (8-OHdG). Sitagliptin inhibited HG-induced production of pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-8 (IL-8) in HrGECs. It also ameliorated HG-induced aggravation of HrGECs permeability and reduction of the tight junction component claudin-5. Moreover, kruppel Like Factor 6 (KLF6) mediated the protective effects of sitagliptin on endothelial monolayer permeability against HG. Collectively, sitagliptin reversed the HG-induced oxidative stress, inflammation, and increased permeability in HrGECs via regulating KLF6. This study suggests that sitagliptin might be implicated as an effective strategy for preventing diabetic renal injuries in the future.